Device‐Assisted and Neuromodulatory Therapies for Parkinson's Disease: A Network Meta‐Analysis. Issue 9 (22nd July 2022) - Rajan, Roopa; Garg, Kanwaljeet; Srivastava, Achal. K; Singh, Manmohan
Abstract: Background: Device‐assisted and neuromodulatory therapies are the standard of care for Parkinson's disease (PD) with disabling motor complications. We aimed to compare and rank the currently available advanced therapies for PD on patient relevant outcomes. Methods: We searched various databases for randomized controlled trials that studied subthalamic nucleus deep brain stimulation (STN‐DBS), globus pallidus interna (GPi) DBS, pallidotomy, subthalamotomy, continuous subcutaneous apomorphine infusion (CSAI), or intrajejunal levodopa infusion (IJLI), in patients with PD and motor complications. Primary outcome was the quality of life (QOL) at 6 months. Secondary outcomes included Unified Parkinson's Disease Rating Scale III and II, ON time, OFF time, levodopa equivalent daily doses, and adverse events (AE). Data were pooled using a Bayesian network meta‐analysis, summarized as mean difference (MD) with 95% credibility intervals (CrI) and visualized in forest plots/league tables. Surface under the cumulative ranking curve plots determined the ranking probability. Results: We identified 6745 citations and included 26 trials. STN‐DBS (MD, −8.0; 95% CrI, −11, −5.8), GPi‐DBS (MD, −7.1; 95% CrI, −11, −2.9), and IJLI (MD, −7.0; 95% CrI, −12, −1.8) led to better QOL than medical therapy alone, without significant differences among them. STN‐DBS had the highest probability of being ranked the best treatment for QOL (79.6%), followed by IJLI (63.5%) and GPi‐DBS (62.8%). Conclusions: In advanced PD, STN‐DBS alleviates more patient and clinician relevant outcomes, followed by GPi‐DBS and IJLI. In resource limited settings, unilateral pallidotomy may improve motor symptoms and activities of daily living, although overall QOL may not be improved. © 2022 International Parkinson and Movement Disorder Society.